19.5k views
1 vote
Simplify -3d^-8(-4d^-14)

2 Answers

5 votes

Answer:

12 / d^22.

Explanation:

-3d^-8(-4d^-14)

= (-3*-4) d^(-8+-14)

= 12d^-22

= 12 /d^22.

User Gwyneth
by
4.1k points
4 votes

Answer:


\large\boxed{12d^(-22)=(12)/(d^(22))}

Explanation:


(-3d^(-8))(-4d^(-14))=\bigg((-3)(-4)\bigg)\bigg((d^(-8))(d^(-14))\bigg)\\\\\text{use}\ a^n\cdot a^m=a^(n+m)\\\\=12d^(-8+(-14))=12d^(-22)


\text{You can use}\ a^(-n)=(1)/(a^n)\\\\12d^(-22)=12\cdot(1)/(d^(22))=(12)/(d^(22))

User Kostub Deshmukh
by
5.1k points